Pola Asuh Orang Tua Terhadap Pekembangan Sosial Emosional Anak Usia Dini di Paud Tunas Bangsa Desa Padamulya Kecamatan Pasirkuda Kabupaten Cianjur - Komala Rosanti, Rita; Zultiar, Indra; Ashshidiqi Poppyariyana, Alfian (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The aim of this research is to determine the role of parenting styles, emotional support, and parental involvement in the social-emotional development of early childhood at PAUD Tunas Bangsa. This research collects data through interviews, observation and documentation. The research results show that parents use democratic parenting styles. With a permissive parenting style that gives children complete freedom, discipline and boundaries are difficult to create. On the contrary, this parenting style allows children to learn responsibility and become more confident. Even though time constraints are a major obstacle, consistent emotional support from parents has been proven to create a good environment for children's learning. The active involvement of parents in the parenting program at PAUD Tunas Bangsa has a positive impact on the relationship between parents and children. In addition, this involvement increases parents' understanding of good ways to care for children. Play-based methods shape children's character and social skills. Parents like this method. However, the hope is that people learn the academic basics gradually. Developing more organized parenting programs, providing parent guidelines, increasing parental involvement in school activities, and optimizing play-based approaches are some of the research recommendations.